On the estimation of free-surface turbulence using ultrasonic sensors. (April 2018) - Zhang, G.; Valero, D.; Bung, D.B.; Chanson, H.
Abstract: Accurate determination of free-surface dynamics has attracted much research attention during the past decade and has important applications in many environmental and water related areas. In this study, the free-surface dynamics in several turbulent flows commonly found in nature were investigated using a synchronised setup consisting of an ultrasonic sensor and a high-speed video camera. Basic sensor capabilities were examined in dry conditions to allow for a better characterisation of the present sensor model. The ultrasonic sensor was found to adequately reproduce free-surface dynamics up to the second order, especially in two-dimensional scenarios with the most energetic modes in the low frequency range. The sensor frequency response was satisfactory in the sub-20 Hz band, and its signal quality may be further improved by low-pass filtering prior to digitisation. The application of the USS to characterise entrapped air in high-velocity flows is also discussed. Highlights: Ultrasonic sensors' performance for the determination of dynamic free-surface levels is examined. Synchronized high-speed camera imaging is employed for comparison. Ultrasonic sensors' performance for dry conditions, 2D waves and 3D free-surface roughness is analysed. Ultrasonic sensors capabilities in air-water flows are discussed.